Conversion of quinoa and lupin agro-residues into biochar in the Andes: An experimental study in a pilot-scale auger-type reactor - Heredia Salgado, Mario A.; Coba S, Jonathan A.; Cianferoni, A.; Säumel, Ina; Tarelho, Luís A. C. (Frontiers in Bioengineering and Biotechnology, 2022)
In the last decades, the cultivation of quinoa and lupin became an important source of income for Andean farmers due to the demand for high nutrient-density foods from the Global North. The increase in the cultivation intensity caused by this exogenous demand led to the overexploitation of local ecosystems and a decrease in soil fertility. As an alternative to recover and improve soil quality, this work uses a pilot-scale auger pyrolysis reactor, implemented in the Andes, to assess the conversion of the agro residues generated in the post-harvesting processes of quinoa and lupin into biochar for soil amendment. Following the European Biochar Certificate guidelines, the pyrolyzed quinoa stems can be classified as biochar while the pyrolyzed quinoa husks can be classified as pyrogenic carbonaceous material. Both can be used for soil amendment considering their molar ratios (H/Corg, O/Corg) and carbon content. It was not possible to carbonize lupin stems and seedcases. Despite the altitude (2632 m.a.s.l), the CO concentration during the carbonization of quinoa stems and husks were 1024.4 and 559 mg/Nm3, this last, near the European eco-design standard of 500 mg/Nm3. A subsequent SWOT analysis showed the need to explore low-cost and low-complexity pyrolysis reactors that allow the decentralized conversion of agro residues at the farm-scale. The development of local standards to regulate the production and use of biochar is also essential to grant the safety of the processes, the quality of the products, and mobilize funds that allow implementation at relevant scales.